Electromagnetic interference in a multiconductor transmission system – MTL - Ciocioi, I; Nae, V (Scientific Bulletin ("Mircea cel Bătrân" Naval Academy), 2019)
In electrical and electronic practice, many connection and transmission elements (cables) are used as a multi-conductor transmission lines (MTL). The electromagnetic fields existing in the environment of these multiconductor transmission lines and can generate different types of coupling phenomena, causing EMC problems by the appearance of the unwanted EMI, disturbing the correct function and altering the information. Electromagnetic coupling between the circuits/cables of a circuit (also known as crosstalk) can also occur between the signal and power paths of an assembly made on printed circuit boards, PCB (printed board circuit), so it is important that when designing such an electrical / electronic circuit, these aspects should be taken into account.